KAJIAN EKONOMI WILAYAH DAN KELEMBAGAAN USAHA PETERNAKAN AYAM RAS PETELUR DI KABUPATEN TASIKMALAYA (The Spatial and Institutional Economic Analysis of Layer Broiler Farming in The District of Tasikmalaya) - Andre R Daud; Hasni Arief (Universitas Muhammadiyah Purwokerto, 2009)
The theme of this study is the spatial economic of layer-broiler production in Tasikmalaya district. The study was accomplished in eight months, from April to November 2008. Its purpose is twofold; first, to identify the spatial economic of layer-broiler production; and second, to describe the properties of its institutional performance. The data was collected through surveys, and subsequently analyzed by means of localization indices, specialization indices, LQ and the structure – conduct – performance (SCP) approach. The analysis revealed that layerbroiler farming on the area yet have not enough contributed to the regional economic of Tasikmalaya. In addition, the aspect of availability and accessibility to feed resources, and the aspect of marketing have been identified as a critical point for further development of layer-broiler industry in the future. Keyword : spatial economic, localization, specialization, LQ, SCP.